2006
DOI: 10.1097/01.aco.0000192820.76353.3e
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic surgical patient

Abstract: According to World Health Organization projections, anesthesiologists can expect to care for more diabetic patients than ever before. Diabetes and its associated complications present unique challenges to the perioperative physician. As biomedical research continues to unravel the genetic, cellular and molecular mechanisms of this complex metabolic disease, our specialty must be prominently involved in the design and testing of innovative treatments to protect the diabetic patient from the risks of surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 88 publications
0
14
0
1
Order By: Relevance
“…There are 20.8 million children and adults in the US, or 7% of the population, who have diabetes and at this rate it is estimated that one in every 400 children and adolescents has diabetes mellitus [1]. The World Health Organization predicts that anesthesiologists can expect to care for more diabetic patients than ever before [2]. It has been demonstrated that an elevation of perioperative serum glucose levels as well as hyperinsulinemia contribute to impaired monocyte function leading to increased postoperative infections and patient mortality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There are 20.8 million children and adults in the US, or 7% of the population, who have diabetes and at this rate it is estimated that one in every 400 children and adolescents has diabetes mellitus [1]. The World Health Organization predicts that anesthesiologists can expect to care for more diabetic patients than ever before [2]. It has been demonstrated that an elevation of perioperative serum glucose levels as well as hyperinsulinemia contribute to impaired monocyte function leading to increased postoperative infections and patient mortality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These include minimally invasive surgeries and neuraxial anesthesia. 7,36,37 Surgery itself causes a reduction in insulin sensitivity, which is proportional to the length and technique of the procedure. Thorell and coworkers 37 demonstrated that cholecystectomy preformed as a laparoscopy caused significantly less reduction in insulin sensitivity compared to that of a conventional open surgical technique.…”
Section: Preoperative Blood Glucose Effects On Intraoperative Carementioning
confidence: 99%
“…Predictors of death were ischemic heart disease, urgent surgery, American Society of Anesthesiologists physical status score, and hyperglycemia. 7,8 A high blood glucose (BG) level is one component of anesthetic care that may need more stringent control, as evidenced by many studies, but tight control may also have negative outcomes as shown in the data from the Normoglycemia in Intensive Care EvaluationSurvival Using Glucose Algorithm Regulation (NICE-SUGAR) study. 9 NICE-SUGAR is a large multicenter study published in April 2009, which included 6104 intensive care unit (ICU) patients in three different countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidences have shown that the mortality in pa ents with non cardiac 5 surgery was 24% at one year. Ischemic heart disease, urgent surgery, higher American Society of Anesthesiologists (ASA) physical status score and hyperglycemia were the major 5,6 predictors of increased periopera ve mortality. Periopera ve blood sugar control was the major component of anesthe c care that may need more stringent control but ght control of blood sugar level may also have nega ve outcomes as shown in the data from the Normoglycemia in Intensive Care Evalua on-Survival Using Glucose Algorithm 7 Regula on (NICE-SUGAR) study.…”
Section: Introductionmentioning
confidence: 99%